2017
DOI: 10.18632/oncotarget.17431
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant EML4-ALK rearrangement and EGFR mutation in non-small cell lung cancer patients: a literature review of 100 cases

Abstract: The discovery of EGFR mutations and EML4-ALK gene rearrangements has radically changed the therapeutic scenario for patients with advanced non-small cell lung cancer. ALK and EGFR tyrosine-kinase inhibitors showed better activity and efficacy than standard chemotherapy in the first and second line treatment settings, leading to a clear advantage in overall survival of advanced non-small cell lung cancer patients harboring these genetic alterations.Historically the coexistence of EGFR mutations and EML4-ALK rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 59 publications
2
41
0
Order By: Relevance
“…[ 5 6 10 ] Patients housing both mutations have shown an objective response and increased sensitivity to ALK-TKI alone[ 11 12 ] but can also be sensitive to both targeted therapies, thus suggesting a variable dependence on EGFR and ALK oncogenes. [ 13 ] Patients with double mutations have a higher incidence of brain metastases[ 14 ] and also renal dissemination as seen in our case, indicating their aggressive nature.…”
supporting
confidence: 53%
See 3 more Smart Citations
“…[ 5 6 10 ] Patients housing both mutations have shown an objective response and increased sensitivity to ALK-TKI alone[ 11 12 ] but can also be sensitive to both targeted therapies, thus suggesting a variable dependence on EGFR and ALK oncogenes. [ 13 ] Patients with double mutations have a higher incidence of brain metastases[ 14 ] and also renal dissemination as seen in our case, indicating their aggressive nature.…”
supporting
confidence: 53%
“…Rearrangement of ALK with echinoderm microtubule-associated protein-like-4 oncogene on the chromosome-2 short arm in approximately 3%–7% NSCLC adenocarcinoma cases specific for ALK-TKIs such as crizotinib and ceritinib. [ 14 ] EGFR mutations have been known to predominate in well-differentiated while ALK in poorly differentiated adenocarcinomas[ 15 16 ] in young Asian nonsmokers. [ 4 ] However, around 100 cases of concomitant presence have been reported in the world[ 14 ] and only one case in India.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…www.nature.com/scientificreports www.nature.com/scientificreports/ with such co-mutations is of clinical importance since these concurrent mutations represent a distinct subset of patients and may have significant impact on treatment outcomes. In this regard, previous studies showed that patients carrying EGFR/ALK co-mutations varied in their sensitivity to and that the choice between these two classes of TKI drugs as first-line treatment for these patients is still being debated 49 . Hence, further studies are required to investigate clinical activity and drug sensitivity of different co-mutation subsets in order to develop suitable treatment approaches.…”
Section: Discussionmentioning
confidence: 99%